Pertanggungjawaban Pidana Perzinahan Menurut KUHP dan Hukum Adat Baduy - Apriyaldo Apriyaldo; Hasuri Hasuri; Fitria Agustin (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2023)
Adultery is a problem that often occurs in Indonesia, adultery itself is an act that often occurs in society due to a lack of awareness and norms. Adultery in the Criminal Code is regulated in Article 411 which is a complaint offense, without a complaint from the party who feels aggrieved cannot be criminalized. The purpose of this research is to find out the criminal responsibility for adultery according to the Criminal Code and Baduy Customary Law, and to find out the comparison of punishments for adultery according to the Criminal Code and Baduy Customary Law, this study uses an empirical normative approach. by using primary data sources, namely data obtained directly from the source, secondary data obtained from existing sources such as journals, books and laws while tertiary data obtained from websites and others related to writing this thesis. As for the research results obtained by the author that criminal liability for adultery according to the Criminal Code is regulated in article 411 with a maximum imprisonment of 1 year in prison or a maximum fine of category II of IDR 10,000,000.00 (ten million rupiah). Meanwhile, according to the Baduy tribe, adultery is a disgrace that embarrasses all parties, both the victim, the perpetrator and the Baduy community. So that both married and unmarried people still commit adultery. The punishment is to be sent to prison for 40 days, perform a self-purification ceremony (ngabokoran) and then get married.